Roles of Soybean Plasma Membrane Intrinsic Protein GmPIP2;9 in Drought Tolerance and Seed Development - Lu, Linghong; Dong, Changhe; Liu, Ruifang; Zhou, Bin; Wang, Chuang; Shou, Huixia (Frontiers in Plant Science, 2018)
Aquaporins play an essential role in water uptake and transport in vascular plants. The soybean genome contains a total of 22 plasma membrane intrinsic protein (PIP) genes. To identify candidate PIPs important for soybean yield and stress tolerance, we studied the transcript levels of all 22 soybean PIPs. We found that a GmPIP2 subfamily member, GmPIP2;9, was predominately expressed in roots and developing seeds. Here, we show that GmPIP2;9 localized to the plasma membrane and had high water channel activity when expressed in Xenopus oocytes. Using transgenic soybean plants expressing a native GmPIP2;9 promoter driving a GUS-reporter gene, it was found high GUS expression in the roots, in particular, in the endoderm, pericycle, and vascular tissues of the roots of transgenic plants. In addition, GmPIP2;9 was also highly expressed in developing pods. GmPIP2;9 expression significantly increased in short term of polyethylene glycol (PEG)-mediated drought stress treatment. GmPIP2;9 overexpression increased tolerance to drought stress in both solution cultures and soil plots. Drought stress in combination with GmPIP2;9 overexpression increased net CO2 assimilation of photosynthesis, stomata conductance, and transpiration rate, suggesting that GmPIP2;9-overexpressing transgenic plants were less stressed than wild-type (WT) plants. Furthermore, field experiments showed that GmPIP2;9-overexpressing plants had significantly more pod numbers and larger seed sizes than WT plants. In summary, the study demonstrated that GmPIP2;9 has water transport activity. Its relative high expression levels in roots and developing pods are in agreement with the phenotypes of GmPIP2;9-overexpressing plants in drought stress tolerance and seed development.